A comprehensive computational investigations on the physical properties of TiXSb (X: Ru, Pt) half‐Heusler alloys and Ti2RuPtSb2 double half‐Heusler. Issue 9 (30th December 2021) - Rached, Youcef; Caid, Messaoud; Merabet, Mostefa; Benalia, Salaheddine; Rached, Habib; Djoudi, Lakhdar; Mokhtari, Mohamed; Rached, Djamel
Abstract: In this paper, we have investigated the structural, elastic, optoelectronic and thermoelectric properties of the new half‐Heusler alloys TiXSb (X: Ru, Pt) and Ti2 RuPtSb2 double half‐Heusler compound, using the full‐potential linearized augmented plane wave method. Different approximations for the exchange‐correlation functional were performed as generalized gradient approximation + Hubbard potential (GGA +  U ) and its combination with the modified Becke–Johnson potential. The negative values of the calculated formation energy indicate that these compounds are energetically stable. Both half Heusler alloys are half‐metallic ferromagnetic materials and exhibit an integer magnetic moment of Mt = 1.00 μB . While, the Ti2 RuPtSb2 is a direct semiconductor at center symmetry. The calculations of optical properties revealed that Ti2 RuPtSb2 compound exhibits an excellent optical efficiency. The thermoelectric properties such as the Seebeck coefficient ( S ); electronic thermal conductivity ( κ e / τ ), power factor (PF), and figure of merit (ZT) have been studied and discussed in detail. Consequently, the investigated compounds were identified as candidate materials for high technological applications. Abstract : Motivated by the double half‐Heusler alloys and their ternary compositions, herein we present a computational study on the physical properties of TiXSb (X: Ru, Pt) and Ti2 RuPtSb2 compounds using the first‐principle plane wave method in the framework of density functional theory. Both half Heusler alloys are half‐metallic ferromagnetic materials and exhibit an integer magnetic moment of Mt = 1.00 μB . While, the Ti2 RuPtSb2 is a direct semiconductor at center symmetry. The calculations of optical properties revealed that Ti2 RuPtSb2 compound exhibits an excellent optical efficiency. According to the obtained results, the investigated compounds were identified as candidate materials for high technological applications.